Appraising Multinuclear Cu2+ Structure Formation in Cu‐CHA SCR Catalysts via Low‐T Dry CO Oxidation with Modulated NH3 Solvation. Issue 9 (13th September 2022) - Iacobone, Umberto; Nova, Isabella; Tronconi, Enrico; Villamaina, Roberta; Ruggeri, Maria Pia; Collier, Jillian; Thompsett, David
Abstract: Cu 2+ ions (ZCu 2+ (OH) −, Z2 Cu 2+ ) are regarded as the NH3 ‐SCR (SCR=selective catalytic reduction) active site precursors of Cu‐exchanged chabazite (CHA) which is among the best available catalysts for the abatement of NOx from Diesel engines. During SCR operation, copper sites undergo reduction (Reduction half‐cycle, RHC: Cu 2+ →Cu + ) and oxidation (Oxidaton half‐cycle, OHC: Cu + →Cu 2+ ) semi cycles, whose associated mechanisms are still debated. We recently proposed CO oxidation to CO2 as an effective method to probe the formation of multinuclear Cu 2+ species as the initial low‐T RHC step. NH3 pre‐adsorption determined a net positive effect on the CO2 production: by solvating ZCu 2+ (OH) − ions, ammonia enhances their mobility, favoring their coupling to form binuclear complexes which can catalyze the reaction. In this work, dry CO oxidation experiments, preceded by modulated NH3 feed phases, clearly showed that CO2 production enhancements are correlated with the extent of Cu 2+ ion solvation by NH3 . Analogies with the SCR‐RHC phase are evidenced: the NH3 ‐Cu 2+ presence ensures the characteristic dynamics associated with a second order kinetic dependence on the oxidized Cu 2+ fraction. These findings provide novel information on the NH3 role in the low‐T SCR redox mechanism and on the nature of the related active catalyst sites. Abstract : Time‐dependent NH3 feed enables to modulate the NH3 loading on Cu‐CHA catalysts for NH3 ‐SCR. Dry CO‐to‐CO2 oxidation runs – with variable extents of NH3 pre‐adsorption – probe the formation of Cu 2+ multinuclear species only when NH3 solvates the Cu 2+ sites, thus supporting recent novel findings on the dual‐site nature of the low‐T SCR‐RHC and highlighting the related central role of NH3 .